The Challenges of UN Peacekeeping Mission in Finding a Solution to Rebel Groups in the East of the Democratic Republic of Congo [Tantangan Misi Penjaga Perdamaian PBB dalam Menemukan Solusi Terhadap Kelompok Pemberontak di Timur Republik Demokratik Kongo] - Ingabire, Landry; Kurniawan, Yandry (Sekretariat Jenderal DPR RI, 2022)
The Democratic Republic of the Congo (DRC) is a country with the longest rebel conflict of the 21st century. This article analyzes the causes of the UN’s difficulties in finding a solution to the crisis of rebel groups which threaten security in the DRC, particularly in its eastern part. Most of the existing work on the subject under study state that the failure of peacekeeping missions in the DRC are due to various factors such as mandate, strength, complexity of violence, etc. However, existing studies have not analyzed the work of MONUSCO as a regime and why this regime is not effective. In approaching the theory of the international regime, this article uses the internal and external factors of the regime to analyze the causes of this ineffective peacekeeping mission in the DRC. Research applies qualitative research methods with data from primary and secondary data obtained from official MONUSCO documents, books, journals, and online news. This article shows that the rebel crisis in the DRC is due to various internal problems and that the MONUSCO principles and rules are ineffective in eradicating the rebel groups which cause insecurity hence deterring peace in the DRC.AbstrakRepublik Demokratik Kongo (DRC) adalah negara dengan konflik pemberontakan terpanjang pada abad ke-21. Artikel ini menganalisis penyebab kesulitan PBB dalam mencari solusi atas krisis kelompok pemberontak yang mengancam keamanan di DRC, khususnya yang terjadi di wilayah bagian timurnya. Sebagian besar tulisan yang sudah ada mengenai subjek yang diteliti menyatakan bahwa kegagalan misi penjaga perdamaian di DRC disebabkan oleh berbagai faktor seperti mandat, kekuatan, kompleksitas kekerasan, dll. Namun, penelitian terdahulu belum pernah menganalisis MONUSCO sebagai rezim dan mengapa rezim ini tidak efektif. Dengan pendekatan teori rezim internasional, artikel ini menggunakan faktor internal dan eksternal rezim untuk menganalisis penyebab tidak efektifnya misi pemeliharaan perdamaian di DRC. Penelitian ini menggunakan metode penelitian kualitatif dengan data primer dan data sekunder yang diperoleh dari dokumen resmi MONUSCO, buku, jurnal, dan berita online. Artikel ini menunjukkan bahwa krisis pemberontak di DRC disebabkan oleh berbagai masalah internal dan bahwa prinsip dan aturan MONUSCO tidak efektif dalam memberantas kelompok pemberontak yang menyebabkan ketidakamanan sehingga menghalangi perdamaian di DRC.